Sea buckthorn pulp and seed oils ameliorate lipid metabolism disorders and modulate gut microbiota in C57BL/6J mice on high-fat diet - Wang, Zhen; Zhou, Shengmin; Jiang, Yuanrong (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD), along with the complications obesity and dyslipidemia, are worldwide lipid metabolism disorders. Recent evidence showed NAFLD could be ameliorated by diet and lifestyles by attenuating gut microbiota dysbiosis via gut-liver axis. Sea buckthorn oils, including sea buckthorn pulp oil (SBPO) and sea buckthorn seed oil (SBSO), were investigated in this study for their beneficial effects on gut-liver axis in C57BL/6J mice on high-fat diet. Dietary SBPO reduced visceral fat accumulation, adipose cell size, serum and hepatic triglyceride and LDL-C levels and hepatic cell damage score; increased gut microbiota diversity with higher abundance of Lactobacillus, Roseburia and Oscillibacter compared with peanut oil (PO). SBSO showed equal or weaker effects compared to SBPO. This study demonstrates that dietary SBPO has potential to ameliorate NAFLD and related metabolic disorders, like obesity and dyslipidemia, by modulating gut microbiota.